Seasonal ventilation controls nitrous oxide emission in the NW Iberian upwelling - Paz, Mercedes de la; Pérez, Fiz F.; Álvarez-Rodríguez, Marta; Bode, Antonio (Progress in Oceanography, 2024)
Despite their small spatial extent, coastal upwelling systems are an important source of oceanic nitrous oxide (NO) to the atmosphere. To date, hot-spot NO emissions have been reported for low oxygen waters of the eastern boundary upwelling systems at their tropical latitudes, but there is a limited number of studies in their “oxygenated” temperate latitudes. This is the first study of the NO cycle in the NW Iberian Upwelling system, where we investigated the seasonality of the NO concentrations and their emissions to the atmosphere, along with the spatial differences in this coastal region in response to the upwelling. Monthly observations were collected from February 2017 to July 2018, in two hydrographic sections within the Ría of Vigo and Ría of A Coruña, two coastal embayments with contrasting response to the upwelling of the Eastern North Atlantic Central Water (ENACW) in the region. NO concentrations ranged between 8.56 to 12.53 nmol kg (94–121 % of saturation) in the shelf, and from 8.62 to 17.60 nmol kg (94–203 % of saturation) inside the rías, with the highest NO concentration at the bottom, which increase as the upwelling progress from April to October. The air-sea fluxes of NO varied between −1.6 to 3.26 µmol m d in the shelf and −1.53 to 7.00 µmol m d inside the rías. Local differences on the ventilation and remineralization pattern drives the seasonality of NO and differences between Ria of Vigo and Ria of A Coruña, being the higher values of NO concentrations and air-sea fluxes registered in the inner Ria of Vigo. Our study reports the NO emissions of an upwelling system in a temperate latitude, where the upwelling waters are central waters relatively well ventilated in terms of oxygen content, behaving as a moderate low net source of NO to the atmosphere compared to tropical upwelling latitudes, characterised by a lower oxygen content. The research and main author’s salary was funded by the INICIO project funded by the Spanish Ministry of Science (CTM2015–74510-JIN). During the writing phase, ...